Bortezomib Reduces the Tumorigenicity of Multiple Myeloma via Downregulation of Upregulated Targets in Clonogenic Side Population Cells - Nara, Miho (Public Library of Science, 2013)
Side population (SP) cells in cancers, including multiple myeloma, exhibit tumor-initiating characteristics. In the present study, we isolated SP cells from human myeloma cell lines and primary tumors to detect potential therapeutic targets specifically expressed in SP cells. We found that SP cells from myeloma cell lines (RPMI 8226, AMO1, KMS-12-BM, KMS-11) express CD138 and that non-SP cells include a CD138-negative population. Serial transplantation of SP and non-SP cells into NOD/Shi-scid IL-2γnul mice revealed that clonogenic myeloma SP cells are highly tumorigenic and possess a capacity for self-renewal. Gene expression analysis showed that SP cells from five MM cell lines (RPMI 8226, AMO1, KMS-12-BM, KMS-11, JJN3) express genes involved in the cell cycle and mitosis (e.g., CCNB1, CDC25C, CDC2, BIRC5, CENPE, SKA1, AURKB, KIFs, TOP2A, ASPM), polycomb (e.g., EZH2, EPC1) and ubiquitin-proteasome (e.g., UBE2D3, UBE3C, PSMA5) more strongly than do non-SP cells. Moreover, CCNB1, AURKB, EZH2 and PSMA5 were also upregulated in the SPs from eight primary myeloma samples. On that basis, we used an aurora kinase inhibitor (VX-680) and a proteasome inhibitor (bortezomib) with RPMI 8226 and AMO1 cells to determine whether these agents could be used to selectively target the myeloma SP. We found that both these drugs reduced the SP fraction, though bortezomib did so more effectively than VX-680 due to its ability to reduce levels of both phospho-histone H3 (p-hist. H3) and EZH2; VX-680 reduced only p-hist. H3. This is the first report to show that certain oncogenes are specifically expressed in the myeloma SP, and that bortezomib effectively downregulates expression of their products. Our approach may be useful for screening new agents with which to target a cell population possessing strong tumor initiating potential in multiple myeloma.